A Study on Developing Social Justice Mission and Legal Education among Tribal Communities: Empowering Tribal Communities through Legal Education (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Social justice is justice in terms of the distribution of wealth, opportunities, and privilegeswithin a society. In Western and Asian cultures, the concept of social justice has often referred to theprocess of ensuring that individuals fulfill their societal roles and receive what was their due fromsociety and the requirement for development in legal schooling turned into a main issue during the postpioneer period. These worries were legitimate, as in the nature of legal schooling will undoubtedly affectthe nature of legal interaction and organization of equity in a majority rule country like India.To havesuch a lively and incorporated educational program, the Law Colleges need to foster broad legalawareness courses and have to foster new showing instructional method in the educating of meaningfullaws. Such an educational plan would urge the understudies to move their concentration from simpledoctrinal comprehension of law to useful arrangement and its social ramifications. Social justice is notpossible at grand level unless and until we educate under privileged about their legal rights and awarethem about the laws protecting their rights.